RESEARCH OF THE MAIN DIRECTIONS OF FORECASTING OF COST INDICATORS OF DEVELOPMENT OF AVIATION ENGINEERING - A. Zinchenko; N. Cherner; M. Bobrova (Вестник университета, 2016)
Authors have analysed features of cost forecasting on development of aviation engineering of new generation. It is shown that modeling of both the process of development, and its technical and economic indicators presents certain difficulties. The factors influencing reducing cost of development of perspective aviation engineering are revealed and also the main directions of cost reduction on its development are offered.